Relationship between Diabetes Self-Management Knowledge and Stress Levels of Diabetic Mellitus Patients Who Follow a Diet During the Covid-19 Pandemic in Working area of the Piru Health Center - La Rakhmat Wabula; Endah Fitriasari; Mursalim Saman (Jambura Nursing Journal, 2023)
Patients with Type II Diabetes Mellitus need to improve the Self-Management diet to prevent acute complications and reduce the risk of long-term complications and to do a fairly strict diet that causes boredom and stress because they have to follow dietary recommendations throughout their lives. The purpose of this study was to determine the relationship between diabetes self-management knowledge and stress in type II diabetes mellitus patients on a diet in Telaga Piru Hamlet, West Seram District, SBB Regency. The research design used quantitative research with a cross sectional approach and the number of samples was 93 respondents using total sampling, the instrument was a questionnaire and the analysis used the Spearman rank test. The results showed that the results of the analysis obtained a p-value of 0.000. Thus it is smaller than the level α = 0.05. This means that the hypothesis (H1) is accepted, that is, there is a relationship between diabetes self-management knowledge and the stress of type II diabetes mellitus sufferers on a diet. This can be proven by the value of the significance level, which means that the better self-management knowledge, the lighter the stress of going on a diet in people with type II diabetes mellitus. The results of this study are expected so that diabetes can implement good self-management dietary behavior and can reduce stress felt by sufferers independently.